Avian Physiology: Are Birds Simply Feathered Mammals? - Scanes, Colin G. (Frontiers in Physiology, 2020)
There are marked differences between the physiology of birds and mammals. These reflect the evolutionary distance between the two classes with the last common ancestor estimated as existing 318 million years ago. There are analogous organ systems in birds and mammals. However, marked differences exist. For instance, in the avian gastro-intestinal tract, there is a crop at the lower end of the esophagus. This functions both to store feed and for microbial action. The avian immune system lacks lymph nodes and has a distinct organ producing B-lymphocytes, namely the bursa Fabricius. The important of spleen has been largely dismissed until recently. However, its importance in both innate and specific immunity is increasingly recognized. There is a major difference between birds and mammals is the female reproductive system as birds produce large yolk filled eggs. The precursors of the yolk are synthesized by the liver. Another difference is that there is a single ovary and oviduct in birds.